Desarrollo de un modelo tridimensional de la pelvis por medio del método del elemento finito - Araujo Monsalvo, Víctor Manuel; Domínguez Hernández, Víctor Manuel; Urriolagoitia Calderón, Guillermo (Revista Mexicana de Ingenieria Biomedica, 2004)
There is described the development of a three-dimensional model of a bone of the human hip by means of the method of the finite element. The geometry of the bone decided across 84 courts tomographies practiced the bone of the hip of a patient of feminine sex, 60 years, 1.55 m, 70 kg of weight, before the surgical intervention. Once digitized the cuts tomographies, there fed the information obtained to the software Ansys version 6.1. The developed model consisted of 95,943 elements and of 160,220 nodes. This model will serve as a reference to different cases in which it is needed of Studying and Analyzing the biomechanics of a bone of the hip submitted to charges, and in the cases where prosthesis and implants are applied for the hip.